Adolescent Smoking Behaviour of Depok City Year 2024 - Mary Liziawati; Zakiah Zakiah; Ihyani Nurdiena Marliamara; Faika Rachmawati; Raden Putri Annisya Affriany Prasetyo; Darwati Darwati; Puji Lestari (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Tobacco use remains a significant public health issue in Indonesia. Adolescents are considered capable of making their own decisions, including the choice to smoke. According to the Global Adult Tobacco Survey (GATS) 2021, the smoking prevalence in Indonesia is 33.5%, equivalent to 68.8 million people. This study aims to analyze the factors influencing smoking behavior among adolescents. The results of this study emphasize the importance of greater attention and action to smoking prevention efforts among adolescents, especially among males and those in the older age group. The interventions focused on health education and raising awareness of the dangers of smoking which need to be enhanced, as well as involving family and schools to create a supportive environment therefore the adolescents can make healthier decisions. Furthermore, these results can serve as a basis for the development of more effective policies to address the issue of smoking among adolescents in Indonesia. The research employed a descriptive quantitative method with a cross-sectional design. A total of 5,181 respondents were selected using simple random sampling, and data were collected using a questionnaire. The findings reveal that daily smoking behavior among adolescents is still relatively high, with 11.7% of respondents smoking every day. The majority of respondents were male (70.78%), with the largest age groups being 15 years (21.3%) and 14 years (20.6%). Bivariate analysis using the Chi-Square test indicated a significant relationship between smoking behavior and both age and gender, with a p-value of 0.000 (p < 0.05). These results suggest that male adolescents and older age groups are more likely to engage in smoking behavior than their counterparts.